Vegetable oils as sustainable inks for additive manufacturing: a comparative study [data] - Vázquez-Martel, Clara; Becker, Lukas; Liebig, Wilfried V.; Elsner, Peter; Blasco, Eva (Universität, 2021)
The use of biobased materials in additive manufacturing is arising as a promising approach to modernize the polymer industry reducing its environme...